Effect of the COVID-19 pandemic on the educational indicators in the Dentistry Career of the University of Costa Rica = Efecto de la pandemia por COVID-19 en los indicadores educativos de la Licenciatura en Odontología de la Universidad de Costa Rica - Gutiérrez Marín, Natalia 1975-; Gómez Fernández, Adrián José 1980-; Castro Sancho, Cristina 1970- (2025)
This study aimed to determine the effect of the COVID-19 pandemic on the educational indicators of students who enrolled in the dentistry program at the University of Costa Rica between 2015 and 2021. Records of 522 students were analyzed, considering variables such as gender, age at entry, nationality, marital status, children, place and type of high school attended, and course performance. Information was extracted from the Student Applications System, physical records, and the Civil Registry of Costa Rica. Descriptive and bivariate analyses were performed to identify patterns and correlations between variables, and approval rates before and during the pandemic were evaluated. Seventy percent of the students were women, predominantly Costa Rican, aged between 19 and 23, from public high schools, and originating from the Greater Metropolitan Area. Terminal efficiency was zero due to the closure of clinical courses in 2020, which prevented the 2015 to 2017 cohorts from graduating within 12 semesters. The dropout rate was highest in the first and second semesters, with a progressive decrease in subsequent semesters. Most cohorts experienced delays, particularly in semesters 7-8 and 9-10. First-attempt approval rates increased in some service courses with virtualization during the pandemic, such as Intensive General Chemistry and Elementary Mathematics, but no difference was observed in the courses specific to the School of Dentistry. The COVID-19 pandemic had varying impacts on educational indicators, with virtualization improving performance in some theoretical courses while posing challenges in those with practical and clinical components.
El objetivo del estudio fue determinar el efecto que tuvo la pandemia por COVID-19 en los indicadores educativos de las cohortes de estudiantes que ingresaron a la Licenciatura en Odontología de la Universidad de Costa Rica entre los años 2015 y 2021. Se analizaron datos de 522 expedientes estudiantiles, considerando variables como sexo, edad de ingreso, nacionalidad, estado civil, hijos, lugar y tipo de colegio de procedencia, y desempeño en los cursos. La información fue extraída del Sistema de Aplicaciones Estudiantiles, registros físicos y el Registro Civil de Costa Rica. Se realizaron análisis descriptivos y bivariados para identificar patrones y correlaciones entre variables, evaluando las tasas de aprobación antes y durante la pandemia. El 70% de los estudiantes fueron mujeres, la mayoría costarricenses, entre los 19 y 23 años, provenientes de colegios públicos y originarios de la Gran Área Metropolitana. La eficiencia terminal fue 0 debido al cierre de los cursos clínicos en 2020, lo que impidió que las cohortes del 2015 al 2017 se graduaran en 12 ciclos. El abandono se dió principalmente en los ciclos 1 y 2, con una disminución progresiva en ciclos posteriores. La mayoría de las cohortes presentaron rezago, especialmente en los ciclos 7-8 y 9-10. Las tasas de aprobación en el primer intento aumentaron en algunos cursos de servicio con la virtualización durante la pandemia, como Química General Intensiva y Matemática Elemental, pero en los cursos propios de la FOd-UCR no hubo una diferencia. La pandemia por COVID-19 afectó de manera diferente los indicadores educativos, destacándose que la virtualización mejoró el rendimiento en algunos cursos teóricos, pero presentó dificultades en aquellos con componentes prácticos y clínicos.
En revista Odóvtos, vol. 27, no.1 (enero-abril 2025)
Descripción basada en el contenido visto el 23 de abril, 2025
También disponible en formato HTML y EPUB